The Effect of Perceptions of Women's Leadership on Organisational Culture at the Association of Women's Organisations in Tasikmalaya City - Yuliani, Nadya Amalia; Hamdan, Ahmad; Laksono, Bayu Adi (Journal of Feminism and Gender Studies, 2025)
This research aims to determine the influence of women's leadership perceptions on organizational culture at the Gabungan Organisasi Wanita in Tasikmalaya. The research method used is correlational with a quantitative approach. The sampling technique used was a saturated sampling technique by taking the entire population, namely 46 people. The results of the hypothesis test show that the tcount value for the female leadership perception variable has a value of 2.523 > a ttablel value of 2.00324. Meanwhile, the probability value is 0.015 < alpha 0.05 or 5% so it can be concluded that H0 is rejected and H1 is accepted. The coefficient value for the independent variable is 0.355, which is positive for the dependent variable. This means that the higher the perception of women's leadership in an organization, the higher the level of organizational culture tends to be. Then the results of the R-Square determination analysis show that the perception of women's leadership has an influence of 12.6%. This means that the ability of the independent variable to explain variations in the dependent variable is very limited. Meanwhile, the correlation results show a value of 0.355, indicating that the perception of women's leadership and organizational culture has a low relationship. Thus, based on the results of the analysis, it can be concluded that the perception of women's leadership has a positive influence on organizational culture.